Shared Decision Making at the Limit of Viability: A Blueprint for Physician Action - Daboval, Thierry; Shidler, Sarah; Thomas, Daniel (Université d'Ottawa | University of Ottawa, 2016)
To document interactions during the antenatal consultation between parents and neonatologist that parents linked to their satisfaction with their participation in shared decision making for their infant at risk of being born at the limit of viability.
Keywords: Adult; Canada; Female; Gestational Age; Humans; Male; Parents; Patient Satisfaction; Physician-Patient Relations; Physicians; Pregnancy; Premature Birth; Referral and Consultation; Decision Making